IMPROVING STUDENT’S SPEAKING ABILITY BY IMPLEMENTING TWO STAY TWO STRAY METHOD - Jazilatul Aufah; Mukminatus Zuhriyah; Ria Kamilah Agustina (Universitas islam Negeri Alauddin Makassar, 2021)
Students get difficulty in speaking because they are nervous to express their ideas or thoughts directly and experience mispronunciations. The teacher should choose the best method to make the students improve their speaking ability. Therefore, the researchers focused their study on improving students’ speaking ability by implementing Two Stay Two Stray method. Collaborative classroom action research was used as the research design in this research whose purposes were to describe the teacher’s and the students’ activities in the implementation of TSTS method and the supporting and obstructing factors found by the teacher when implementing TSTS method as well as to know whether or not TSTS could improve the student’s speaking ability. The subjects of this research were 15 students at class VII A of MTs Al- Washoya. Meanwhile, the data were taken from the students’ speaking test and the observation. Data analysis showed that the teacher’s and the students’ activities were as what was written in the lesson plan. The supporting factors were the students’ enthusiasm and motivation in joining speaking class and the obstructing factors were that TSTS spent much time and caused the students’ confusion in the first meeting. Then, the students’ speaking ability got significant improvement in cycle two. Thus, it could be concluded that the implementation of TSTS method could improve the students’ speaking ability.